2004
DOI: 10.4314/sajas.v34i2.3815
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, true metabolisable energy content and amino acid availability of grain legumes for poultry

Abstract: Samples of sweet yellow lupins (Lupinus luteus; n = 4), broad leaf lupins (Lupinus albus; n = 12), narrow leaf lupins (Lupinus angustifolius; n = 8), faba beans (Vicia faba; n = 2), field peas (Pisum sativum; n = 4) and narbon beans (Vicia narbonensis; n = 2) were collected over a two-year period. The physical characteristics (thousand seed and hectolitre mass), chemical composition (dry matter, ash, crude protein (CP), ether extract, acid detergent fibre, neutral detergent fibre and mineral content), energy v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
0
15
0
3
Order By: Relevance
“…These values were higher than the values found in the present study. Brand et al (2004) found the CP level of narbon beans to be 23. 7% and Bakoglu et al (2009) found the CP level bitter vetch to be 20.09%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values were higher than the values found in the present study. Brand et al (2004) found the CP level of narbon beans to be 23. 7% and Bakoglu et al (2009) found the CP level bitter vetch to be 20.09%.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the world today there is also a growing resistance against the use of animal protein sources in animal feeding (Brand, 2002). It is desirable, therefore, that the nutritional potential of alternative plant protein feeds, such as grain legumes is fully exploited (Brand et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus concentration varies between 4.2 g/kg (L. angustifolius) and 7.6 g/kg (L. luteus). No extreme differences in trace mineral concentrations occurred except for the manganese concentration of L. albus, which containes approximately 10 times more manganese than the other legume grains (Brand et al, 2004).…”
Section: Nutritional Characteristics Of Soybean Meal Solvent Extract mentioning
confidence: 84%
“…Protein sources are becoming scarcer and more expensive, especially for use in animal feeds (Brand et al, 2004a;Laudadio & Tufarelli, 2011). Depending on the feeding phase (pre-starter, starter, grower or finisher), protein composes up to 22.5% of a balanced diet (Brand & Gous, 2006).…”
Section: Introductionmentioning
confidence: 99%